Study on the relationship between water-logging stress index and yield of spring corn under waterlogging condition in paddy field - YANG Jing-ping; CHEN Jie (浙江大学学报. 农业与生命科学版)
This paper analyzes the corn production function under water-logging condition of paddy field. Based on the experiment of different corn development stage (4, 6, 8 leaf stage) with different waterlogging days (5, 10, 15 days of ground water 10 cm below soil surface) treatments, a corn production function under waterlogging condition of paddy was established. The results showed the relative yield, relative dry matter weight of corn had a significant negative liner relationship with SEW and SDI to the soil watrlogging among the 3 leaf stages of corn. Combined with the relative yield indicators of corn, the SEW and SDI can be used as the index to assess the water-logging effect on the corn yield. Furthermore, it could also be used to give the critical value of water-logging days in the paddy field according to the relative yield requirement.